Daugailiškių tradiciniai palyginimai - Jasiūnaitė, Birutė (Kalbotyra, 1996)
This paper is devoted to analysis of the traditional adjective similes of one of the Eastern Lithuanian dialects. The material taken from this dialect was compared with the facts from the Academical Dictionary of Lithuanian (LKŽ). The analysis showed, that traditional similes in most cases are connected with man and his exterior qualities. The main function of such stereotypes of language can be described by paraphrased formula of B. Whorf: formless item plus a form.